The atherogenic index of plasma: A novel factor more closely related to non-alcoholic fatty liver disease than other lipid parameters in adults - Liu, Jia; Zhou, Liyuan; An, Yu; Wang, Ying; Wang, Guang (Frontiers in Nutrition, 2022)
Background & Aims: The relationship of non-alcoholic fatty liver disease (NAFLD) with the atherogenic index of plasma (AIP) is unclear. This study aims to detect the association between AIP and NAFLD, compare the discriminative power of AIP with other lipid parameters for NAFLD, and establish a discriminant model using physical examination data. Methods: Participants aged over 20 years who underwent routine physical examination in Beijing Chao-yang Hospital from April 2016 to August 2020 were included. We categorized subjects based on hepatic ultrasound results and analyzed the association between NAFLD risk and AIP, conventional plasma lipids, remnant cholesterol (RC), triglyceride and glucose (TyG) index, and other atherogenic indices (n = 112200) using logistic regression, restricted cubic spline regression, and receiver operating characteristic curve. Results: Out of the 112200 subjects, 30.4% had NAFLD. The body weight index, plasma glucose, conventional lipids, TyG index, AIP, atherogenic coefficient (AC), and coronary risk index (CRI) were significantly higher, while HDL-C was lower (p < 0.001) in patients with NAFLD than those without NAFLD (all p < 0.001). Compared with conventional lipids, RC, TyG index, AC, and CRI, AIP had a stronger correlation with the risk of NAFLD (OR 6.71, 95% CI 6.23-7.22, p < 0.001) after adjusting confounders and presented a non-linear dose–response relationship (p < 0.0001). The optimal cut-off value of AIP was 0.05 and the area under the curve (AUC) was 0.82 (95% CI: 0.81-0.82) with high sensitivity and specificity. The AUC of the simplified 3-variable NAFLD discriminant model was 0.90 in both the training set and the validation set. Conclusions: AIP was significantly associated with NAFLD and showed the superior discriminative performance to other lipid parameters. These findings might be helpful for screening NAFLD in high-risk individuals and reducing the prevalence of NAFLD.